Children's social media use behaviors according to parents' social media addiction and methods used by parents - Topan, Aysel; Karakaya, Ayla Gundogdu; Akkoc, Betuel; Kurt, Aylin; Kurt, Aylin (Elsevier Science Inc, 2025)
Aim: The objective of the present study is to ascertain how parents' social media addiction affects their children's social media use behaviors and the methods employed by parents to manage this situation. Method: A cross-sectional study was conducted on a sample of 218 parents of children between the ages of 7-18. The collection of data was facilitated by two instruments: the Parent-Child Information Form and the Social Media Addiction Scale. Results: The present study has revealed that 41.6 % of parents are addicted to social media. Conversely, parents who do not manifest symptoms of social media addiction exhibit a heightened level of awareness regarding their children's social media accounts and demonstrate a more deliberate approach. The predominant methods employed by parents to restrict their children's access to social media included directing them towards sports activities (71.7 %) and fostering peer interaction (37.2 %). Conversely, parents grappling with social media addiction have adopted more stringent measures, including the deliberate confiscation of devices, with the aim of curtailing their children's access to social media. Conclusion: The relationship between parents' social media addiction and their children's social media use is a complex one. While children of addicted parents demonstrate a higher propensity for social media usage, parents endeavour to restrict their children's exposure to this environment. Practical & imath;mplications: Nurses and health professionals can play a pivotal role in raising awareness among families and providing guidance to children on the safe use of the internet. (c) 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Social Media Addiction; Children; Parents